The effect of technology-based interventions on child and parent outcomes in pediatric oncology: A systemic review of experimental evidence - Hazal Ozdemir Koyu; Ebru Kilicarslan Törüner (Elsevier, 2023)
Objective: In recent years, childhood cancers have become an increasingly important health problem worldwide. Evidence shows that technology-based interventions in pediatric oncology are effective, feasible, and acceptable. However, studies in this field are limited. This systematic review was planned to examine the available evidence for the impact of technology-based interventions on children, adolescents with cancer patients, and their parents. Methods: In the systematic review, studies published between 2014 and 2022 from The Cumulative Index to Nursing and Allied Health Literature (CINAHL) Plus with Full Text, Cochrane Library, PsycINFO, ProQuest, PubMed, Science Direct, Scopus, and Web of Science databases were identified using a search strategy. Six studies by the criteria were examined in terms of the technology-based intervention, the intervention's duration, the follow-up period, significant findings, and the theory used in the intervention. The Joanna Briggs Institute (JBI) critical appraisal tools were used to evaluate the quality of the studies. In this systematic review, preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines were followed. Results: A total of six studies met the inclusion criteria: five randomized controlled trials and one quasi-experimental study. In studies for children with cancer, it was determined that the children were between the ages of 6 and 18. It has been determined that technology-based interventions mostly consist of electronic health interventions such as web-based interventions, virtual reality, and digital and mobile health interventions such as messaging, phone contact, and smartphone applications. In the studies, the intervention period ranged from 1 to 1.5 ​h and 10 weeks, and the follow-up periods ranged from 12 weeks to 6 months. In studies for parents, it was observed that the intervention durations ranged from 8 to 12 weeks, and the follow-up periods varied between 3 and 12 months. In most of the studies, technology-based applications have positive effects on the physical and psychological (symptom management, anxiety, stress, coping, and quality of life) problems of children and adolescents. Technology-based interventions affect parents' knowledge levels and coping skills, psychosocial symptoms (anxiety, post-traumatic stress disorder, depression, and caregiver burden), resilience, social support, and self-efficacy. Conclusions: Technology-based interventions have been effective in improving physical and psychological symptoms in children with cancer, and parents' coping and psychosocial symptoms. These results should be interpreted with caution due to the limited number of studies, small sample sizes, and high heterogeneity. Comprehensive and high-quality randomized controlled trials are needed to obtain the best evidence for the effectiveness of technology-based interventions in pediatric oncology. Systematic review registration: PROSPERO registration number was CRD42022297664.